La Cooperacion Sueca en la Universidad Nacional Agraria: Impacto de 26 años de colaboracion - Aleman, F.=700 1 Aguilar, V.
(Es, En)
Ilus., ref.
Keywords: COOPERACION; GESTION; INVESTIGACION; AYUDA AL DESARROLLO; UNIVERSIDADES; SUECIA; NICARAGUA; SAREC; GRADO; POSTGRADO; LA CALERA